2020
DOI: 10.1177/1073191120914403
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of the Comprehensive Assessment of Psychopathic Personality-Self-Report (CAPP-SR) in Lithuanian Offender and Nonoffender Samples

Abstract: The Comprehensive Assessment of Psychopathic Personality (CAPP) is an emerging integrative model that makes use of 33 symptoms to characterize psychopathic personality disorder, but operationalizations of this model have not endured extensive validation to date. The current study sought to validate the recently published CAPP-Self-Report (CAPP-SR). Participants derived from two Lithuanian offender ( n = 231) and nonoffender ( n = 312) samples. They were administered the CAPP-SR, Triarchic Psychopathy Measure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…The instrument has been shown to correlate strongly with other CAPP measures, and exhibits convergent validity with existing self-report measures of psychopathic personality (Sellbom et al, 2019). These findings have been supplemented by recent work within a sample of Lithuanian offenders (Sellbom et al, 2021), which suggested that the CAPP-SR exhibited incremental validity in predicting self-reported aggression as compared to other existing self-report measures (e.g., the Triarchic Psychopathy Measure; Patrick et al, 2009). Though research with the CAPP-SR is still in its infancy, initial results suggest the tool has potential for applied use in forensic and clinical screening settings when resources preclude the use of the more time-and asset-intensive CAPP-IRS.…”
Section: The Comprehensive Assessment Of Psychopathic Personalitymentioning
confidence: 73%
“…The instrument has been shown to correlate strongly with other CAPP measures, and exhibits convergent validity with existing self-report measures of psychopathic personality (Sellbom et al, 2019). These findings have been supplemented by recent work within a sample of Lithuanian offenders (Sellbom et al, 2021), which suggested that the CAPP-SR exhibited incremental validity in predicting self-reported aggression as compared to other existing self-report measures (e.g., the Triarchic Psychopathy Measure; Patrick et al, 2009). Though research with the CAPP-SR is still in its infancy, initial results suggest the tool has potential for applied use in forensic and clinical screening settings when resources preclude the use of the more time-and asset-intensive CAPP-IRS.…”
Section: The Comprehensive Assessment Of Psychopathic Personalitymentioning
confidence: 73%
“…A 4-point rating scale is used to respond to the 99 items, where 1 = false, 2 = mostly false, 3 = mostly true, 4 = true. Studies investigating the CAPP-SR validity have thus far shown promising results (Sellbom et al, 2019(Sellbom et al, , 2021Shou et al, 2020).…”
Section: Comprehensive Assessment Of Psychopathic Personality-self-re...mentioning
confidence: 99%
“…In particular, the relevance of these personality-based PPD models to criminal justice system variables (e.g., violence risk) should be evaluated, as such research has been limited to date (cf. Pedersen et al, 2010;Sellbom et al, 2021).…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAPP-SR has already been described in detail earlier. The Lithuanian translation of the CAPP-SR (Sellbom et al, 2021) was used in the offender sample.…”
Section: Comprehensive Assessment Of Psychopathic Personality-self-re...mentioning
confidence: 99%